A method for plugging formation leakage based on magnesium oxide particle size-activity double-stage hydration phase change

CN122880442APending Publication Date: 2026-10-09CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611188764.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]针对现有技术中的上述不足,本发明的目的在于提供一种基于氧化镁粒径-活性双分级水化相变的破碎地层漏失封堵方法,以解决现有氧化镁基堵漏材料存在的仅对惰性颗粒级配导致多尺度适应性不足、仅靠整体调节固化时间导致可泵送性与快速封堵难以兼顾等问题

Benefits of technology

本发明突破了传统技术单一维度的调控局限,构建了粒径构筑空间、活性调控时序的双分级协同封堵机制。利用粗、中、细粒径差异,分别承担架桥骨架、孔隙填充和微缝密封的物理功能,解决了多尺度裂缝的进入与架桥问题;同时,依据地层温度差异化匹配颗粒活性:在中高温地层将粗粒径设计为低活性以保泵送、构骨架,将中细粒径设计为中高活性以快胶结、填孔隙;在低温地层引入高活性组分以促反应、强封堵。该机制实现了浆体从井筒内可泵送到地层内晶体胶结的定向转化,消除了物理架桥的残余孔隙,显著提升了封堵层的致密性与承压能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122880442A_ABST
    Figure CN122880442A_ABST
Patent Text Reader

Abstract

The application discloses a broken formation leakage plugging method based on magnesium oxide particle size-activity double-stage hydration phase change. The method first identifies the temperature of the leakage formation and the crack width, and prepares a magnesium oxide phase change plugging main agent composed of three particle sizes of coarse, medium and fine; secondly, the hydration activity of the three particle sizes of magnesium oxide is matched according to the formation temperature, and the mass ratio is adjusted according to the crack width; finally, the plugging working slurry is mixed and prepared by mixing the magnesium oxide with a hydration control liquid and a reinforced skeleton material. After being injected into the formation, the slurry body successively experiences the stages of flow filling, standing induction, hydration expansion, cementation reinforcement and pressure bearing stability. The application realizes the "first bridging, then expansion, and then cementation" synergistic plugging of multi-scale cracks, takes into account the pumpability of the wellbore and the rapid phase change plugging in the formation, the plugging layer is dense and has high pressure bearing capacity, and has the characteristics of easy drilling and acidizing plugging removal, and effectively reduces the reservoir damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil and gas drilling and plugging technology, specifically to a method for plugging leaks in fractured formations based on a dual-stage hydration phase change of magnesium oxide particle size and activity. Background Technology

[0002] Loss in fractured formations is a common and complex engineering problem in oil and gas drilling. These formations typically exhibit high levels of fracture development, a wide range of fracture sizes, strong spatial connectivity, and significant heterogeneity in leakage channels. Traditional plugging materials often rely on bridging particles, fiber materials, or cement slurry for sealing. However, bridging materials have low pressure resistance, cement-based materials undergo hydration shrinkage during solidification, and are difficult to unplug after solidification, easily causing reservoir damage.

[0003] The reaction of magnesium oxide with water to form magnesium hydroxide is a typical hydration phase transition reaction (MgO + H₂O → Mg(OH)₂). During the reaction, the solid phase volume increases, resulting in an expansion and filling effect. Furthermore, the product, magnesium hydroxide, is acid-soluble. Therefore, magnesium oxide-based materials possess both expansion-sealing and de-sealing potential. However, existing magnesium oxide-based leak-sealing systems still have the following shortcomings: First, there is a lack of hierarchical matching of the particle size and activity of the core reactant, magnesium oxide. For example, the invention patent CN121495553A proposes a low-density acid-soluble solidification plugging agent that uses limestone powder as the grading rigid particles to achieve large, medium, and small particle size distribution, and limits the overall activity of magnesium oxide to 30%~55%. However, the gradation of this technology only targets the inert framework particles and does not perform hierarchical matching of the particle size and hydration activity of the core reactant, magnesium oxide itself. When faced with multi-level crack networks, ordinary magnesium oxide slurry is difficult to achieve the orderly sealing process of "bridging first, then expansion, and then cementation," and is prone to forming residual pores and interconnected channels inside the sealing layer, resulting in reduced pressure bearing capacity and insufficient adaptability to multi-scale cracks.

[0004] Second, there is a lack of hierarchical control over the hydration behavior of magnesium oxide particles of different sizes. Related academic research (such as the SPE journal article "Comprehensive Study on Curing, Plugging, and Acid-Dissolution of Antipollution MgO-Based Curing Material in Polysulfonate Drilling Fluid") uses self-made MgO-based curing materials in conjunction with drilling fluid for plugging, showing that curing time can be controlled by adjusting the overall MCM dosage or adding a retarder (boric acid). However, this type of method only adjusts the curing time from the perspective of the overall formulation or the addition of a retarder. When facing significant temperature differences in fractured formations, if the activity is too high, it can easily thicken prematurely in the wellbore; if the activity is too low, it is difficult to plug in time. It is difficult to balance wellbore pumpability with rapid phase change plugging within the formation.

[0005] Therefore, there is an urgent need to propose a magnesium oxide dual-stage hydration phase change plugging method that can adapt to changes in formation temperature and fracture scale, so as to achieve efficient, controllable and resolvable plugging of leakage channels in fractured formations. Summary of the Invention

[0006] To address the aforementioned shortcomings in existing technologies, the present invention aims to provide a method for sealing leakage in fractured formations based on a dual-stage hydration phase change of magnesium oxide particle size and activity. This method aims to solve the problems of insufficient multi-scale adaptability due to the fact that existing magnesium oxide-based plugging materials only apply to inert particle gradation, and the difficulty in simultaneously achieving pumpability and rapid sealing by relying solely on overall adjustment of curing time.

[0007] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows: A method for plugging lost circulation in fractured formations based on a dual-level hydration phase change of magnesium oxide particle size and activity is provided, comprising the following steps: S1. Identify the formation temperature T and fracture width W of the lost formation; S2. Prepare a magnesium oxide phase change blocking agent composed of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide; S3. The hydration activity of the coarse-grained, medium-grained, and fine-grained magnesium oxide is graded and matched according to the formation temperature T, and the mass ratio of the coarse-grained, medium-grained, and fine-grained magnesium oxide is adjusted according to the fracture width W. S4. Prepare hydration control liquid and reinforcing skeleton material by mixing the magnesium oxide phase change sealing agent, reinforcing skeleton material and hydration control liquid to prepare a plugging slurry. S5. Inject the plugging slurry into the leakage channel, and sequentially go through the stages of flow filling, static induction, hydration expansion, cementation reinforcement and pressure stabilization to achieve the sealing of the leakage channel; In step S2, the magnesium oxide phase change blocking agent is composed of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide; the coarse-grained magnesium oxide has a particle size of 80-200 mesh, the medium-grained magnesium oxide has a particle size of 200-325 mesh, and the fine-grained magnesium oxide has a particle size of less than 325 mesh.

[0008] Preferably, in step S3, the specific rules for matching activity classification based on formation temperature T are as follows: When T < 60℃, at least one of the coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide shall be highly active magnesium oxide. When 60℃≤T≤120℃, low-activity magnesium oxide is used for coarse-particle magnesium oxide, medium-activity magnesium oxide is used for medium-particle magnesium oxide, and medium-activity or controllable-activity magnesium oxide is used for fine-particle magnesium oxide. When T > 120℃, low-activity magnesium oxide is used for coarse-grained and medium-grained magnesium oxide, while surface-controlled active magnesium oxide is used for fine-grained magnesium oxide.

[0009] Magnesium oxide activity was classified by citric acid method: ≤15s was high activity magnesium oxide, 15-30s was medium activity magnesium oxide, and >30s was low activity magnesium oxide.

[0010] Preferably, in step S3, the specific rule for adjusting the mass ratio based on the crack width W is as follows: When W < 0.5 mm, the mass ratio of coarse, medium, and fine-grained magnesium oxide is (5-20):(30-50):(40-60). When 0.5mm≤W<2mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (20-35):(35-50):(20-35); When 2mm≤W≤8mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (35-60):(25-45):(10-25); When W > 8 mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (35-60):(25-45):(10-25); and the proportion of the reinforcing skeleton material needs to be increased to construct a high-strength support skeleton.

[0011] Preferably, the coarse-grained magnesium oxide has a particle size of 80-200 mesh, the medium-grained magnesium oxide has a particle size of 200-325 mesh, and the fine-grained magnesium oxide has a particle size of less than 325 mesh.

[0012] Preferably, by weight, the hydration regulating liquid comprises: 50-120 parts water, 2-30 parts reaction induction regulator, 0.5-10 parts retarder, 0.2-5 parts suspension stabilizer, and 0.5-5 parts water loss reducing agent.

[0013] Preferably, the reaction-inducing regulator is selected from one or more of magnesium salts, phosphates, and silicates; the retarder is selected from one or more of borates, gluconates, citrates, and saccharides; the suspension stabilizer is selected from one or more of hydroxyethyl cellulose, carboxymethyl cellulose, xanthan gum, and bentonite. The water-loss reducing agent is selected from one or more of bentonite, microsilica, quartz powder, talc, and carboxymethyl cellulose.

[0014] Preferably, the reinforcing skeleton material includes an acid-soluble skeleton material and a fiber-reinforcing material.

[0015] Preferably, the acid-soluble skeleton material is selected from one or more of calcium carbonate, magnesium carbonate, dolomite powder, and acid-soluble mineral particles, with a particle size of 100μm-3mm; the fiber reinforcement material is selected from one or more of biodegradable polyester fiber, polypropylene fiber, calcium carbonate whiskers, magnesium salt whiskers, and glass fiber, with a length of 1-12mm.

[0016] Preferably, in step S4, the magnesium oxide phase change plugging agent, the reinforcing skeleton material, and the hydration regulating liquid are mixed at a mass ratio of 1.0:(0.1-3.5):(0.5-1.5).

[0017] The beneficial effects of this invention are as follows: This invention overcomes the limitations of traditional single-dimensional control technologies by constructing a dual-level synergistic plugging mechanism that integrates particle size construction space and activity regulation timing. Utilizing the differences in coarse, medium, and fine particle sizes, they respectively undertake the physical functions of bridging framework, pore filling, and micro-crack sealing, solving the problems of multi-scale fracture entry and bridging. Simultaneously, particle activity is matched according to formation temperature differences: in medium- and high-temperature formations, coarse particles are designed with low activity to ensure pumpability and framework construction, while medium- and fine particles are designed with medium- to high activity for rapid cementation and pore filling; in low-temperature formations, highly active components are introduced to promote reaction and strong plugging. This mechanism achieves the directional transformation of slurry from the wellbore to crystal cementation within the formation, eliminating residual porosity from physical bridging and significantly improving the compactness and pressure-bearing capacity of the plugging layer. Attached Figure Description

[0018] Figure 1 A schematic diagram of the blocking process of staged hydration phase transition; Figure 2 A schematic diagram showing particle size matching under different slit width conditions; Figure 3 This is a schematic diagram of the "bridging-filling-expansion-bonding" process. Figure 4 Schematic diagram of the microstructure of the sealing layer at different hydration times; Figure 5 This is a schematic diagram illustrating the compressive strength (drillability) of a solidified body. Figure 6 Hydration rate curves for different dosages of highly active magnesium oxide; Figure 7 The hydration rate curves are shown for different amounts of low-activity magnesium oxide. Detailed Implementation

[0019] The specific embodiments of the present invention are described below to enable those skilled in the art to understand the present invention. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various changes are obvious as long as they are within the spirit and scope of the present invention as defined and determined by the appended claims. All inventions utilizing the concept of the present invention are protected.

[0020] A method for plugging lost circulation in fractured formations based on magnesium oxide particle size-activity dual-level hydration phase change includes the following steps: Step 1: Identification of Lost Formation Parameters Based on the leakage rate, pump pressure changes, formation temperature, well depth, drilling fluid density, return status, and logging data during drilling, determine the temperature T and fracture width W of the lost formation.

[0021] The fracture width W can be determined through leakage rate inversion, well leakage model calculation, core fracture observation, imaging logging data, or indoor fracture simulation experiments.

[0022] Based on the crack width W, leakage channels are classified into the following types: Microcrack type: W < 0.5 mm; Small to medium crack type: 0.5 mm ≤ W < 2 mm; Medium to large crack type: 2 mm ≤ W ≤ 8 mm; Large crack or fracture zone type: W > 8 mm.

[0023] Based on formation temperature T, hydration environments are classified into the following types: Low-temperature strata: T < 60℃; Medium-temperature strata: 60℃ ≤ T ≤ 120℃; High-temperature strata: T > 120℃.

[0024] Step 2: Preparation of magnesium oxide phase change plugging agent The magnesium oxide phase change plugging agent is composed of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide.

[0025] The coarse-grained magnesium oxide has a particle size of 80-200 mesh and accounts for 20%-60% of the total mass of the magnesium oxide phase change plugging agent. This component is mainly used to form an initial bridging skeleton in medium and large cracks and to provide slow expansion support during subsequent hydration.

[0026] Medium-sized magnesium oxide has a particle size of 200-325 mesh and accounts for 25%-55% of the total mass of the magnesium oxide phase change plugging agent. This component is mainly used to fill the pores between coarse particles and to generate magnesium hydroxide crystals through a mid-term hydration reaction, thereby improving the bonding strength of the plugging layer.

[0027] Fine-grained magnesium oxide has a particle size of less than 325 mesh and accounts for 10%-45% of the total mass of magnesium oxide phase change plugging agent. This component is mainly used to enter microcracks, fine pores and uneven parts of crack walls, and achieve microscale sealing through subsequent hydration expansion and crystal growth.

[0028] The magnesium oxide can be obtained by calcining, crushing, screening or surface conditioning of magnesium carbonate, magnesium hydroxide, magnesite or other magnesium-containing precursors.

[0029] Step 3: Magnesium oxide particle size-activity dual-level matching Based on formation temperature T and fracture width W, magnesium oxide particle size and activity are matched in a two-level manner.

[0030] When T < 60℃, to avoid the hydration reaction being too slow at low temperatures, at least one of the coarse-grained magnesium oxide, medium-grained magnesium oxide, and fine-grained magnesium oxide should be highly active magnesium oxide.

[0031] When 60℃≤T≤120℃, low-activity magnesium oxide is used for coarse-grained magnesium oxide, medium-activity magnesium oxide is used for medium-grained magnesium oxide, and medium-activity or controllable-activity magnesium oxide is used for fine-grained magnesium oxide, so that the plugging slurry maintains fluidity during the pumping stage and gradually undergoes hydration and expansion after entering the formation.

[0032] When T > 120℃, low-activity magnesium oxide is used for coarse and medium-sized magnesium oxide, while controllable-activity magnesium oxide is used for fine-sized magnesium oxide, in order to avoid premature thickening of the wellbore due to rapid hydration of magnesium oxide under high temperature conditions.

[0033] The activity of the magnesium oxide is controlled by calcination temperature, calcination time, particle size, surface conditioning layer, and hydration regulator. The controllable active magnesium oxide refers to magnesium oxide whose hydration reaction rate is specifically designed and controlled according to formation temperature and plugging sequence requirements through surface conditioning and other technologies; its activity test values ​​can cover low, medium, and high activity ranges, but this invention mainly focuses on customized activity characteristics matched to formation temperature.

[0034] Magnesium oxide activity was classified by citric acid method: ≤15s was high activity magnesium oxide, 15-30s was medium activity magnesium oxide, and >30s was low activity magnesium oxide.

[0035] Based on the crack width W, the preferred gradation of the magnesium oxide phase change sealing agent is as follows: When W < 0.5 mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (5-20): (30-50): (40-60).

[0036] When 0.5mm≤W<2mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (20-35):(35-50):(20-35).

[0037] When 2mm≤W≤8mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (35-60):(25-45):(10-25).

[0038] When W > 8 mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (35-60):(25-45):(10-25); and the proportion of the reinforcing skeleton material needs to be increased to construct a high-strength support skeleton.

[0039] Step 4: Preparation of hydration regulating solution The hydration conditioning solution comprises the following components in parts by weight: Water: 50-120 parts; Reaction induction regulator: 2-30 parts; Retarder: 0.5-10 parts; Suspension stabilizer: 0.2-5 parts; Water loss reducer: 0.5-5 parts.

[0040] The reaction induction regulator is selected from one or more of magnesium salts, phosphates, and silicates, and is used to adjust the hydration reaction environment of magnesium oxide and the composition of the cementing phase.

[0041] The retarder is selected from one or more of borates, gluconates, citrates, and sugar compounds, and is used to delay the initial hydration rate of magnesium oxide to ensure that the plugging slurry has sufficient pumpable time.

[0042] The suspension stabilizer is selected from one or more of hydroxyethyl cellulose, carboxymethyl cellulose, xanthan gum, and bentonite, and is used to improve the suspension stability of magnesium oxide particles, acid-soluble skeleton materials, and fiber-reinforcing materials in slurry.

[0043] The water loss reducing agent is used to reduce the amount of filtration loss of the plugging slurry on the crack wall and in the pore medium, and to prevent the slurry from losing water too early and thus reducing its fluidity.

[0044] The water loss reducing agent is selected from one or more of bentonite, microsilica, quartz powder, talc powder, and carboxymethyl cellulose, and is used to reduce the water loss rate of the sealing material.

[0045] Step 5: Preparation of reinforcing framework material The reinforcing skeleton material includes acid-soluble skeleton material and fiber-reinforcing material, with a ratio of (20~40):(8~15).

[0046] The acid-soluble framework material is selected from one or more of calcium carbonate, magnesium carbonate, dolomite powder, and acid-soluble mineral particles, with a particle size of 100μm-3mm.

[0047] The acid-soluble skeleton material is used to form a rigid support skeleton in large fractures or fracture zones, and can be dissolved by acid in subsequent acidizing operations to reduce reservoir damage.

[0048] The fiber reinforcement material is selected from one or more of biodegradable polyester fiber, polypropylene fiber, calcium carbonate whiskers, magnesium salt whiskers, and glass fiber, and has a length of 1-12 mm.

[0049] The fiber-reinforced material is used to form an entangled network in the cracks, improving the erosion resistance, tensile strength, shear strength, and overall toughness of the sealing layer.

[0050] Step 6: Prepare the sealing slurry The magnesium oxide phase change sealing agent, reinforcing skeleton material and hydration control liquid are mixed in a mass ratio of (1.0):(0.1-3.5):(0.5-1.5) and stirred evenly to obtain the sealing slurry.

[0051] For microfractured lost formations, the amount of reinforcing skeleton material added should be 0.1-0.5 times the mass of the magnesium oxide phase change plugging agent.

[0052] For small to medium fractured lost circulation formations, the amount of reinforcing skeleton material added should be 0.5-1.5 times the mass of the magnesium oxide phase change plugging agent.

[0053] For medium to large fractured lost circulation formations, the amount of reinforcing skeleton material added should be 1.0 to 2.5 times the mass of the magnesium oxide phase change plugging agent.

[0054] For large fractures or broken zone-type lost circulation formations, the amount of reinforcing skeleton material added should be 2.0-3.5 times the mass of the magnesium oxide phase change plugging agent.

[0055] The plugging slurry remains in a fluid state at ground circulation temperature, and its pumping time is 1-4 hours.

[0056] Step 7: Injection and Staged Hydration Phase Change Blocking The plugging slurry is pumped into the lost formation through a drill string, annulus, or a dedicated injection string.

[0057] After the plugging slurry enters the leakage channel, it goes through the following stages in sequence: The first stage is the fluid filling stage. Under the action of pressure difference, the plugging slurry enters the fracture network. Coarse-sized particles form initial bridging in large fractures, medium-sized particles fill the pores between coarse particles, and fine-sized particles enter micro-fractures and irregular areas on the fracture walls.

[0058] The second stage is the static induction stage. After circulation stops, the plugging slurry gradually enters the hydration induction period under the influence of formation temperature. The hydration control fluid inhibits the early rapid reaction of magnesium oxide, causing the slurry to undergo significant thickening and hydration after injection.

[0059] The third stage is the hydration and expansion stage. Magnesium oxide reacts with water to form magnesium hydroxide crystals. The hydration products grow in the pores between particles and the micro-gaps on the crack walls, resulting in volume expansion and increasing the density of the sealing layer.

[0060] The fourth stage is the cementation and reinforcement stage. As the hydration reaction continues, magnesium hydroxide crystals intertwine and grow, forming a magnesium salt composite cement phase with the reaction-inducing regulator in the hydration control solution, thus transforming the sealing layer from a particle-stacking structure to a crystalline cement structure.

[0061] The fifth stage is the pressure stabilization stage. The sealing layer forms a multi-scale composite structure in the fracture, consisting of "coarse-grained skeleton - medium-grained filling - fine-grained sealing - hydrated crystal cementation - fiber network reinforcement", achieving stable sealing of leakage channels in the fractured formation.

[0062] Step 8: Pressure Testing and Unblocking After curing is complete, a pressure test is conducted. Once the pressure-bearing capacity of the sealing layer reaches the design value, normal drilling operations are resumed.

[0063] When it is necessary to remove the reservoir section plugging, acid treatment can be used to acidify the plugging layer. The magnesium hydroxide, calcium carbonate, magnesium carbonate, and magnesium salt cement phases in the plugging layer are dissolved under the action of acid, thereby restoring the flow capacity of fractures or pore channels.

[0064] Example 1: Sealing of medium-temperature, large-fracture formations 1. Application Conditions The formation temperature is 85℃, and the width of the leakage fractures is 2-5mm, which belongs to the medium-temperature medium-to-large fracture type of leakage formation.

[0065] 2. Preparation of magnesium oxide phase change plugging agent Prepare 100 parts of magnesium oxide phase change plugging agent, wherein: 45 parts of coarse-grained, low-activity magnesium oxide, with a particle size of 80-200 mesh; 35 parts of medium-sized active magnesium oxide with a particle size of 200-325 mesh; 20 parts of fine-particle-size controllable active magnesium oxide, with a particle size of less than 325 mesh.

[0066] Among them, coarse-grained low-activity magnesium oxide is used to form a crack skeleton, medium-grained medium-activity magnesium oxide is used to fill the skeleton pores, and fine-grained controllable-activity magnesium oxide is used for microcrack sealing and subsequent hydration expansion.

[0067] 3. Preparation of hydration regulating solution Take 80 parts by weight of water, 10 parts by weight of reaction induction regulator, 3 parts by weight of retarder, 1.5 parts by weight of suspension stabilizer and 2 parts by weight of water loss reducer, stir evenly to obtain hydration control solution.

[0068] 4. Preparation of reinforcing skeleton materials Take 120 parts of acid-soluble calcium carbonate particles with a particle size of 0.2-1.0 mm; take 8 parts of biodegradable polyester fiber with a length of 6 mm; mix them evenly to obtain the reinforcing skeleton material.

[0069] 5. Preparation of Leak-Plugging Grout By weight, 100 parts of magnesium oxide phase change sealing agent, 128 parts of reinforcing skeleton material and 90 parts of hydration control liquid are mixed and stirred evenly to obtain the sealing slurry.

[0070] The plugging slurry maintains good fluidity at ground circulation temperature, meeting the requirements for wellbore pumping.

[0071] 6. Injection and Curing The plugging slurry was pumped into the simulated crack plate, with the crack width set to 3 mm. After injection, circulation was stopped, and the plate was allowed to cure at 85°C.

[0072] After the sealing slurry enters the crack, coarse-sized magnesium oxide and calcium carbonate particles first form a bridging framework; medium-sized magnesium oxide continues to fill the pores of the framework; and fine-sized magnesium oxide enters the micropores and irregular areas of the crack walls. Subsequently, the magnesium oxide undergoes a hydration reaction to generate magnesium hydroxide crystals, and the sealing layer gradually expands and densifies.

[0073] 7. Effects The sealing layer formed after curing has good integrity and pressure resistance, and can effectively seal medium-temperature and medium-to-large crack-type leakage channels.

[0074] Example 2: Sealing of High-Temperature Wide-Fractured Formations 1. Application Conditions The formation temperature is 135℃ and the fracture width is 5-8mm, which belongs to the high-temperature wide fracture type of lost formation.

[0075] 2. Preparation of magnesium oxide phase change plugging agent Prepare 100 parts of magnesium oxide phase change plugging agent, wherein: 55 parts of coarse-grained, low-activity magnesium oxide, with a particle size of 80-200 mesh; 30 parts of medium-sized to medium-active magnesium oxide with a particle size of 200-325 mesh; 15 parts of fine-particle-size controllable active magnesium oxide, with a particle size of less than 325 mesh.

[0076] Under high-temperature conditions, coarse and medium-sized magnesium oxides use low-activity components, while fine-sized magnesium oxides use surface-modified controllable active components to avoid premature thickening inside the wellbore.

[0077] 3. Preparation of hydration regulating solution Take 90 parts by weight of water, 8 parts of reaction induction regulator, 5 parts of retarder, 2 parts of suspension stabilizer, and 3 parts of water loss reducer, stir evenly to obtain hydration control solution.

[0078] 4. Preparation of reinforcing skeleton materials Take 200 parts of acid-soluble skeleton particles with a particle size of 0.5-2.0 mm; take 12 parts of fiber reinforcement material with a length of 8 mm; mix them evenly to obtain the reinforcement skeleton material.

[0079] 5. Preparation of Leak-Plugging Grout 100 parts of magnesium oxide phase change sealing agent, 212 parts of reinforcing skeleton material and 100 parts of hydration conditioning liquid were mixed to obtain the sealing slurry.

[0080] 6. Injection and Curing The plugging slurry was injected into a high-temperature simulated fracture. Because the activity of magnesium oxide matches that of the high-temperature formation, the slurry did not undergo significant premature thickening during the pumping stage; after entering the fracture, it sequentially formed a particle bridging, pore filling, hydration expansion, and crystalline cementation structure.

[0081] 7. Effects The cured sealing layer has high erosion resistance and pressure bearing capacity, and is suitable for sealing leakage in high-temperature, wide-fracture formations.

[0082] Example 3: Microfracture sealing 1. Application Conditions The formation temperature is 65℃, and the fracture width is less than 0.5mm, which belongs to the microfractured type of lost formation.

[0083] 2. Preparation of magnesium oxide phase change plugging agent Prepare 100 parts of magnesium oxide phase change plugging agent, wherein: 10 parts of coarse-grained, low-activity magnesium oxide; 40 parts of medium-sized active magnesium oxide; 50 parts of fine-particle-size controllable active magnesium oxide.

[0084] The high proportion of fine-grained magnesium oxide in this formulation facilitates its entry into microcracks and the fine pores on the crack walls.

[0085] 3. Preparation of hydration regulating solution Take 75 parts water, 5 parts reaction induction regulator, 2 parts retarder, 1 part suspension stabilizer, and 1.5 parts water loss reducer by weight, stir evenly to obtain hydration control solution.

[0086] 4. Preparation of Leak-Plugging Grout Mix 100 parts of magnesium oxide phase change sealing agent, 30 parts of a small amount of acid-soluble fine particulate material, and 85 parts of hydration control liquid to obtain a microcrack sealing slurry.

[0087] 5. Injection and Curing After the plugging slurry enters the microfractures, fine-grained magnesium oxide preferentially penetrates to the depths of the microfractures and undergoes a hydration reaction under the influence of formation temperature, forming magnesium hydroxide crystals. The combined effect of crystal growth and volume expansion gradually and densely fills the microfractures.

[0088] 6. Effects This system is suitable for sealing microcracks and small leakage channels, and can improve the sealing effect of small-scale cracks that are difficult to seal with ordinary bridging materials.

[0089] Comparative Example 1: Anhydrous Conditioning Liquid System Compared with Example 1, this comparative example does not add hydration control liquid, but only mixes magnesium oxide phase change sealing agent with water. The solid phase of the system is very easy to settle, which cannot meet the requirements of the leak sealing operation.

[0090] Comparative Example 2: Magnesium oxide system without activity fractionation Compared to Example 2, this comparative example uses highly active magnesium oxide for coarse, medium, and fine particle sizes. Under high-temperature formation conditions, the hydration reaction of this system starts too quickly, and the viscosity of the slurry rises rapidly during pumping, causing premature thickening and injection difficulties in the wellbore, making it difficult to seal deep leakage channels.

[0091] In order to quantitatively evaluate the sealing effect of the plugging slurry provided by the present invention, the pressure bearing capacity and leakage of the sealing layer formed after curing in Examples 1-3 were tested, and the test results are shown in Table 1.

[0092] Table 1. Blocking performance test results of different embodiments

[0093] Note: "Leakage" refers to the sealing strip breaking down during the test, resulting in a complete leak.

[0094] As can be seen from the test results in Table 1, Examples 1 and 2 both exhibited high pressure resistance and low leakage under medium-temperature medium-to-large fractures and high-temperature wide fractures, with dense and highly stable plugging layers. Example 3 also achieved effective plugging of micro-fractured formations. In contrast, the comparative example failed to achieve effective plugging due to the lack of hydration regulation or activity grading matching.

[0095] Figures 1 to 3The phase change plugging process, particle size matching strategy, and synergistic plugging mechanism are presented respectively. To further analyze the microscopic mechanism and material properties behind the particle size-activity dual-level synergistic plugging mechanism of this invention, the following is combined with... Figures 4 to 7 Detailed analysis: Figure 4 The hydration evolution process of active magnesium oxide was visually demonstrated. Needle-like structures appeared in the slurry after 2.5 hours of hydration and gradually developed into rod-like shapes. This microscopic morphological feature revealed the growth and interweaving process of magnesium hydroxide crystals in the interparticle gaps. It confirmed at the microscopic level that the hydration reaction can effectively fill the pores and provide a solid material basis for the formation of a dense and high-strength sealing layer.

[0096] Figure 5 The engineering applicability of the material was verified by compressive strength testing. The maximum compressive strengths of the solidified products of the system were 0.43, 0.83, and 1.68 MPa, respectively, which are much lower than those of conventional cement stone (greater than 10 MPa). This indicates that the solidified body of the present invention belongs to an easily drillable plugging system, which can not only meet the pressure requirements for temporary plugging, but also avoid the problems of difficult drilling and removal and easy damage to the reservoir after traditional cement plugging, thus demonstrating excellent reservoir protection characteristics.

[0097] Figure 6 The study revealed the complex hydration kinetics of highly active magnesium oxide. Its exothermic peak showed a fluctuating trend of first decreasing, then increasing, and then decreasing again with increasing dosage. In particular, rapid hydration and a large amount of exothermic phenomena occurred at a medium dosage (30%). This result, from the opposite perspective, confirms the necessity of the activity classification in this invention: if the highly active components are not controlled, they are very likely to cause uncontrolled and violent reactions in the wellbore. This provides key experimental basis for the selection of low-activity components in high-temperature formations to ensure construction safety.

[0098] Figure 7 The study showed the variation of the hydration exothermic peak of low-activity magnesium oxide with increasing dosage. The first exothermic peak gradually decreased while the second exothermic peak steadily increased, indicating that the low-activity component can effectively inhibit the initial dissolution and hydration, providing a sufficient safe pumping window for deep well operations, while ensuring that the effective component fully participates in the hydration reaction in the later stage.

[0099] In summary, this invention, through the synergistic design of particle size and activity, successfully overcomes the technical bottleneck of traditional magnesium oxide-based materials in achieving both pumpability and plugging performance under complex working conditions, and realizes efficient, pressure-bearing, and easy-to-unblock integrated plugging of leakage channels in fractured formations.

[0100] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for plugging lost circulation in fractured formations based on a dual-stage hydration phase change of magnesium oxide particle size and activity, characterized in that, Includes the following steps: S1. Identify the formation temperature T and fracture width W of the lost formation; S2. Preparation of magnesium oxide phase change blocking agent composed of magnesium oxide with different particle sizes; S3. The hydration activity of magnesium oxide with different particle sizes is classified and matched according to the formation temperature T, and the mass ratio of magnesium oxide with different particle sizes is adjusted according to the fracture width W. S4. Prepare hydration control liquid and reinforcing skeleton material by mixing the magnesium oxide phase change sealing agent, reinforcing skeleton material and hydration control liquid to prepare a plugging slurry. S5. Inject the plugging slurry into the leakage channel to seal the leakage channel.

2. The method according to claim 1, characterized in that, In step S2, the magnesium oxide phase change blocking agent is composed of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide; the coarse-grained magnesium oxide has a particle size of 80-200 mesh, the medium-grained magnesium oxide has a particle size of 200-325 mesh, and the fine-grained magnesium oxide has a particle size of less than 325 mesh.

3. The method according to claim 2, characterized in that, In step S3, the specific rules for activity classification matching based on formation temperature T are as follows: When T < 60℃, at least one of the coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide shall be highly active magnesium oxide. When 60℃≤T≤120℃, low-activity magnesium oxide is used for coarse-particle magnesium oxide, medium-activity magnesium oxide is used for medium-particle magnesium oxide, and medium-activity or controllable-activity magnesium oxide is used for fine-particle magnesium oxide. When T > 120℃, low-activity magnesium oxide is used for coarse-grained magnesium oxide and medium-grained magnesium oxide, while controllable-activity magnesium oxide is used for fine-grained magnesium oxide. Magnesium oxide activity was classified by citric acid method: ≤15s was high activity magnesium oxide, 15-30s was medium activity magnesium oxide, and >30s was low activity magnesium oxide.

4. The method according to claim 2, characterized in that, In step S3, the specific rules for adjusting the mass ratio based on the crack width W are as follows: When W < 0.5 mm, the mass ratio of coarse, medium, and fine-grained magnesium oxide is (5-20):(30-50):(40-60). When 0.5mm≤W<2mm, the mass ratio of coarse, medium and fine magnesium oxide particles is (20-35):(35-50):(20-35); When 2mm≤W≤8mm, the mass ratio of coarse, medium and fine magnesium oxide particles is (35-60):(25-45):(10-25). When W > 8 mm, the mass ratio of coarse-grained magnesium oxide, medium-grained magnesium oxide and fine-grained magnesium oxide is (35-60):(25-45):(10-25); and the proportion of the reinforcing skeleton material needs to be increased to construct a high-strength support skeleton.

5. The method according to claim 1, characterized in that, By weight, the hydration control liquid comprises: 50-120 parts water, 2-30 parts reaction induction regulator, 0.5-10 parts retarder, 0.2-5 parts suspension stabilizer, and 0.5-5 parts water loss reducer.

6. The method according to claim 5, characterized in that, The reaction induction regulator is selected from one or more of magnesium salts, phosphates, and silicates; the retarder is selected from one or more of borates, gluconates, citrates, and sugar compounds; the suspension stabilizer is selected from one or more of hydroxyethyl cellulose, carboxymethyl cellulose, xanthan gum, and bentonite; and the water loss reducing agent is selected from one or more of bentonite, microsilica, quartz powder, talc, and carboxymethyl cellulose.

7. The method according to claim 1, characterized in that, The reinforcing skeleton material includes acid-soluble skeleton material and fiber-reinforcing material.

8. The method according to claim 7, characterized in that, The acid-soluble skeleton material is selected from one or more of calcium carbonate, magnesium carbonate, dolomite powder, and acid-soluble mineral particles, with a particle size of 100μm-3mm; the fiber reinforcement material is selected from one or more of biodegradable polyester fiber, polypropylene fiber, calcium carbonate whiskers, magnesium salt whiskers, and glass fiber, with a length of 1-12mm.

9. The method according to claim 1, characterized in that, In step S4, the magnesium oxide phase change plugging agent, the reinforcing skeleton material and the hydration control liquid are mixed at a mass ratio of 1.0:(0.1-3.5):(0.5-1.5).

Citation Information

Patent Citations

  • Low-density acid-soluble consolidation plugging agent, plugging slurry and drilling plugging method thereof

    CN121495553A